2014
DOI: 10.1159/000357309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neuroimmunomodulatory Activity of Recombinant Human Interferon α

Abstract: Objective: Recombinant human interferon (rhIFN)-α is a potent immunoregulator having a wide range of therapeutic applications. In the present study, rhIFN-α was evaluated for its neuroimmunomodulatory activity. Method: Dose-dependent gene expression of cytokines and chemokines in the brain of rhIFN-administered mice was studied using real-time SYBR green PCR. Results: Statistically significant increase in expression levels of tumor necrosis factor-α, interleukin (IL)-6, IL-1β and IFN-γ were observed. Conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Interferon, has been known to modify the immune response of the CNS-behaviourally as well as neurophysiologically [5,27] and our previous study has shown that exogenously administered rhIFN a can effectively modify cytokine expression in the brain [20]. Our results were similar to that reported by Tohamy et al, where pre treatment of mice with IFN, 24 h before infection delayed the onset of specific rabies signs [31].…”
Section: Discussionsupporting
confidence: 91%
“…Interferon, has been known to modify the immune response of the CNS-behaviourally as well as neurophysiologically [5,27] and our previous study has shown that exogenously administered rhIFN a can effectively modify cytokine expression in the brain [20]. Our results were similar to that reported by Tohamy et al, where pre treatment of mice with IFN, 24 h before infection delayed the onset of specific rabies signs [31].…”
Section: Discussionsupporting
confidence: 91%